Monitoring of Marine Pollution 2019
DOI: 10.5772/intechopen.81685
|View full text |Cite
|
Sign up to set email alerts
|

The Hazards of Monitoring Ecosystem Ocean Health in the Gulf of Mexico: A Mexican Perspective

Abstract: Ecological services provided by the Gulf of Mexico constitute vital assets for the socioeconomic development of the USA, Mexico, and Cuba. This ecosystem houses vast biodiversity and significant fossil fuel reserves. However, its ecological stability and resilience have been jeopardized by anthropogenic disturbances. Massive oil spills (Ixtoc-I, 1979; Deepwater Horizon, 2010) caused severe environmental injuries and unveiled the vulnerability of coastal and deep-sea habitats. Baseline and monitoring studies ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Ukpaka et al (2020) and Gomez-Mellado et al (2020) mention that produced water and drilling cuttings can contribute to the presence of EC in soils contaminated with hydrocarbons, both studies also agree with the results of Botello et al (2019) and Ziarati et al (2019) who add the presence of heavy metals in low areas and sediments of oil spills, of which Reyes et al (2016) have emphasized their effects on health. Also, other studies have observed effects from 0.02 eq L −1 of Na (from the extract of the saturated pasta), since the study area has a vocation for agricultural use, it is necessary to establish pastures and vegetables that can be tolerant to this indicator (Soto et al, 2018;Mendoza-Carranza et al, 2016).…”
Section: Contaminated Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Ukpaka et al (2020) and Gomez-Mellado et al (2020) mention that produced water and drilling cuttings can contribute to the presence of EC in soils contaminated with hydrocarbons, both studies also agree with the results of Botello et al (2019) and Ziarati et al (2019) who add the presence of heavy metals in low areas and sediments of oil spills, of which Reyes et al (2016) have emphasized their effects on health. Also, other studies have observed effects from 0.02 eq L −1 of Na (from the extract of the saturated pasta), since the study area has a vocation for agricultural use, it is necessary to establish pastures and vegetables that can be tolerant to this indicator (Soto et al, 2018;Mendoza-Carranza et al, 2016).…”
Section: Contaminated Soilmentioning
confidence: 99%
“…Due to these low concentrations, some of these sites have been declared below the permissible limits, but in some cases, environmental problems persist affecting the growth and development of plants (Sánchez et al, 2017;Challenger et al, 2018). Hence, Soto et al (2018) and González-Mille et al (2019) highlight the importance of considering methods of identification of these components since they relate them to negative effects on water potential, density, and porosity of the soil.…”
Section: Introductionmentioning
confidence: 99%
“…The economic damages inflicted by the massive oil spill on the general ecological services provided by the GoM to bordering countries like Mexico remain unsettled. In spite of international treaties acknowledged by the two countries, compensatory economic damages to the USA waters by BP amounted to $16.67US billion whereas in the case of Mexico's EZZ, BP did not admit any damage and approved compensatory funds ($1.2US million) to cover for Mexico's emergency monitoring procedures conducted at the outset of the DWH event [9,10].…”
Section: Bmentioning
confidence: 99%